Ethical sensitivity and compassion in home care: Leaders’ views - Blomqvist, Heidi (Nursing ethics, 2023)
BackgroundWith an increasing older population, the pressure on home care resources is growing, which makes it important to ensure the maintenance of quality care. It is known that compassion and ethical sensitivity can improve the quality of care, but little is known about care leaders’ perceptions on ethical sensitivity and compassion in home care and how it is associated with staff competence and thus quality of care.AimThe aim of the study was to explore home care leaders’ perceptions of ethical sensitivity and compassion associated with care quality in home care.Research design, participants, and research contextA hermeneutical approach with a qualitative explorative design was used. The data consists of texts from 10 in-depth interviews with home care leaders. Content analysis was used as a method.Ethical considerationsThe study was conducted following the ethical guidelines of the Declaration of Helsinki and the Finnish Advisory Board of Research Ethics. Research ethics permission was applied for from a Research Ethics Board.FindingsOne overall theme and four subthemes were found. The overall theme was: “Compassion provides deeper meaning and ethical sensitivity provides means for knowing how to act”.DiscussionIf nurses fail to be sensitive and compassionate with patients, good and high qualitative home care cannot be achieved. Ethical sensitivity and compassion can be seen as resources in home care but the organization and the care leaders need to provide the support for these to develop.ConclusionThis study provides an understanding of the meaning of ethical sensitivity and compassion as sources of strength and their link to quality of care in a home care context. Further studies could focus on how to build compassion and ethical sensitivity into home-based care and how to ensure adequate support for healthcare professionals’ compassion and ethical sensitivity.